COMMOGNITIVE PERSPECTIVE ON STUDENTS’ REASONING IN COMPARING MEASURES OF CENTRAL TENDENCY USING FREQUENCY POLYGONS - Rahmatina, Desi; Pratiwi, Endityas; Adinda, Anita (Jurnal Math-UMB.EDU, 2025)
Measures of central tendency, such as the mean, median, and mode, are fundamental concepts in statistics that can be used to support decision-making. The purpose of this study is to describe how university students reason about measures of central tendency when comparing two age distributions of patients presented in the form of frequency polygons, from a commognitive perspective. This study employs a descriptive qualitative method with an exploratory approach. A total of 37 students participated in the study, four of whom were selected as research subjects—two representing the calculative category and two representing the visual-interpretative category. The research instruments consisted of one problem related to measures of central tendency and an interview guide. The problem included three questions, each presenting data in the form of frequency polygons. The data were thematically analyzed using Sfard’s commognitive framework, focusing on four components: word use, visual mediators, routines, and narratives. The findings reveal that students in the calculative category predominantly used visual mediators and routines. In contrast, students in the visual-interpretative category emphasized the use of word use to construct narratives. Keywords: commognitive, reasoning, measures of central tendency, frequency polygon